2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26370
|View full text |Cite
|
Sign up to set email alerts
|

Becoming Boundary Spanning Engineers: Research Methods and Preliminary Findings

Abstract: A growing body of evidence suggests that practicing engineers are increasingly expected to act as boundary spanners who can participate in and manage diverse local and global teams, translate competing stakeholder demands into effective design solutions, and leverage expert knowledge from multiple fields and specialties. The larger project represented by this paper responds to this reality by proposing boundary spanning as a core meta-attribute for engineering students and early career professionals. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Building on the results presented here, our research team is currently collecting interview and reflection data from early career engineers in multiple industry sectors, including students who have held multiple intern or co-op positions and professionals in the first 1-3 years of full-time work. The data from this phase of the study will allow us to identify the most prevalent boundary spanning roles, activities, and competencies associated with early career engineering practice (Jesiek et al, 2016;Jesiek et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on the results presented here, our research team is currently collecting interview and reflection data from early career engineers in multiple industry sectors, including students who have held multiple intern or co-op positions and professionals in the first 1-3 years of full-time work. The data from this phase of the study will allow us to identify the most prevalent boundary spanning roles, activities, and competencies associated with early career engineering practice (Jesiek et al, 2016;Jesiek et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of a larger multiphase research study on boundary spanning in engineering. In previous conference papers, we reported on work carried out to date, including an overview of our qualitative systematic review approach (Jesiek, Mazzurco, Trellinger, & Ramane, 2015) and our preliminary findings from a parallel study of boundary spanning experiences among early career engineers (Jesiek, Trellinger, & Mazzurco, 2016;Jesiek, Trellinger, & Nittala, 2017). Here, we offer a detailed description of our methods, following the guidelines for qualitative systematic reviews (Grant & Booth, 2009) and based on the PRISMA framework (Moher et al, 2009), used here because it provides a well-established and rigorous approach to conducting literature reviews (Borrego et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Previous works have suggested that there is a disconnect between university and industry environments (Stevens et al, 2014; Walther & Radcliffe, 2007), resulting in engineers who are not adequately prepared to successfully collaborate in developing solutions to complex problems. Research focused on characterizing engineering work has explored the types of problems faced in the engineering workforce, how working with people is a part of engineering practice, and the boundaries that engineers must negotiate in their work (Jesiek et al, 2016; Stevens et al, 2014; Trevelyan, 2010). Specific to GEC, case studies and interviews have been analyzed to understand the types of global situations faced by working engineers (Jesiek et al, 2015; Jesiek, Zhu, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An overview of this data analysis process, as well as some preliminary results, are presented in previous conference papers. [20][21] The same three coauthors met to resolve any disagreements and to finalize the codes. Next, all of the researchers met to discuss the most prominent themes with respect to the goals of this paper, namely, which examples best demonstrate what our methodological approach made visible about practice?…”
Section: Discussionmentioning
confidence: 99%